Process evaluation of the midwifery initiated oral health‐dental service program: perceptions of pregnant women. (22nd November 2018) - George, A; Villarosa, AR; Patterson Norrie, T; Hoolsema, J; Dahlen, HG; Ajwani, S; Bhole, S; Blinkhorn, A; Srinivas, R; Yaacoub, A; Milat, A; Skinner, J; et al.
Abstract: Background: Pregnant women in Australia seldom seek dental care and are unaware of its importance. To address these gaps the midwifery‐initiated oral health dental service (MIOH‐DS) program was comprehensive trialled and found effective. The aim of this study was to undertake a process evaluation of the MIOH‐DS using the perspectives of pregnant women who participated in the trial. Methods: A qualitative research design was utilized, whereby content analysis was undertaken on data from 11 semi‐structured interviews with women who participated in the program. Results: All participants were receptive of the MIOH‐DS intervention, and found it to be an acceptable intervention that met their needs, and encouraged future positive oral health practices and health‐seeking behaviours. They expressed that midwives were an appropriate professional to conduct oral health assessments, education and referrals to affordable dental services. Although some participants were initially apprehensive towards receiving treatment during pregnancy, dental staff members were able to appropriately educate and reassure them during treatment. Conclusions: The MIOH‐DS represents a promising and acceptable intervention strategy for pregnant women to promote their oral health. Findings merit further investigation on whether positive outcomes achieved can be sustained when implemented in other national or international settings similar to the study setting.